SOME REMARKS ABOUT CHALLENGES IN SUPPLY CHAIN MANAGEMENT – VALUE CREATION, RISK MANAGEMENT, INNOVATIVENESS AND DEMOGRAPHY - Ziółkowska, Bogusława; Gorzeń-Mitka, Iwona; Sipa, Monika; Skibiński, Andrzej (Advanced Logistic Systems - Theory and Practice, 2016)
Globalisation processes, the development of information technologies, growing expectations of shareholders and increasing changeability of the economic environment force interdependence of activities undertaken by entities operating today. This refers in particular to supply chains understood as a network of organisations involved in a range of flows both in the area of tangible goods and intangible ones. The aim of this paper is to indicate leading modern management challenges facing supply chain participants. It pays attention, among other things, to the issues of risk management, increasing innovativeness, creation of value added for the customer and functioning of supply chains. The discussion presented is a result of literature studies in the area indicated. This study systematically investigates supply chain management literature, with an aim to map out what is the main challenges in supply chain management and what needs to be explored further. The review findings suggest that a majority of existing studies concentrate on value creation, risk management, innovation and demography.